HUBUNGAN KONFORMITAS TERHADAP KELOMPOK DENGAN KEDISIPLINAN SISWA DI SEKOLAH PADA SISWA KELAS II SMU YKM TANJUNGSARI SUMEDANG - Roros Widianingsih; Tati S. D; Agus Abdul Rahman (Psympathic : Jurnal Ilmiah Psikologi, 2009)
In adolescence, conformity aspect in a peer group was one of important aspect in their social life since adolescences need safety and acceptability feeling from their peer group much more than other age group. Teenagers have conformity for their peer group and tend to accept and follow rules and standards adopted by their peer group including changing perception, opinion, behaviors and their attitudes to become more ”acceptable” by their friend in a group.Many teenagers have strong bond with their friends and tend to behave inappropriately with rules and values in society. Indisciplinary behavior conducted at school showed a correlation with their peer group which can be seen from their ”breaking rules” attitudes such as, smoking in the class, inapproapriate clothing, not doing their homework and Research methods used in this research is a correlational model and using Marvin Shaw’s group conformity scale and student’s disciplinary scale from Ausubel. SPSS 11.5 were then used to test the validity and reliability of those two measurement methods. Spearman rank correlation technique dan were used to analyze data taken from 129 students of Grade II SMU YKM Tanjungsari. Statistical analysis conducted in this research was given the result of -0,673 whilst by using testing criterion with significany 5 percent would then concluded that the research hypothese is acceptable.Brief conclusion from this research was given a result that there is a negative relations between conformity toward the peer group with indisciplinary behavior conducted by Grade II students at SMU YKM Tanjungsari.